The potential of forest resource management at farmer groups in the Rarung forest area. Issue 1 (1st December 2022) - Suparyana, P K; Sukardi, L.; Yakin, A.; Amiruddin,; Sa'diyah, H.
Abstract: The conversion of land into agricultural land and the felling of trees in forest areas have an economic impact on the community. These activities if not managed properly will cause many problems. Poor management will cause many problems such as decreased soil fertility, erosion, extinction of flora and fauna, floods, droughts, and even global environmental changes. The purpose of this research is to analyze the economic valuation of agricultural commodities in the Rarung Forest Area. The population of this study are 3 groups of farmers in Pemepek Village, Pringgarata District, Central Lombok Regency with 54 farmers as respondents. Analysis of the data used to perform economic valuation is to calculate the Total Economic Valuation. The results showed that the Rarung Forest Area has a very large natural resource potential with a Total Economic Value of Rp.3.215.553.333, - which consists of an economic value of direct benefits amount Rp.2.925.868.333, - and the economic value of indirect benefits amount Rp.289.685.000, -. Seeing the potential of natural resources in the Rarung Forest Area, the stakeholders may be able to manage, secure, and monitor the area against all pressures and disturbances that occur.